E-Mudharabah Management Information System Design with Cost Benefit Analysis Approach - Andarwati, Mardiana; Swalaganata, Galandaru; Sulaksono, Aditya Galih; Futaqi, Faruq Ahmad (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
The urgency of this research is to provide a solution to these challenges by introducing a technology-based system called e-Mudharabah, leveraging a Decision Support System (DSS) with the Cost Benefit Analysis (CBA) method. The aim of this research is to develop a digital platform that facilitates financing for MSMEs by using the CBA-based DSS to assess business feasibility and reduce the risks associated with the traditional Mudharabah scheme. The novelty of this research lies in the integration of modern technology with Islamic finance principles through the e-Mudharabah platform. Unlike conventional Mudharabah schemes, this platform introduces CBA and DSS to evaluate business feasibility, thus minimizing financial risks. The inclusion of consultants further enhances the process by providing guidance and support to both MSMEs and financiers, ensuring better decision-making and successful partnerships. The implications of this research are impactful for both Islamic financial institutions and MSMEs. The adoption of the e-Mudharabah platform can significantly reduce risks for financiers while improving access to capital for MSMEs. The platform also promotes transparency and fair cooperation in financial transactions, contributing to the sustainability of MSME growth in alignment with Islamic economic principles.